Contextualized tasks of Brazilian textbooks from a critical mathematics education perspective - Amaral-Schio, Rúbia Barcelos [UNESP]; Mazzi, Lucas Carato [UNESP] (My University, 2021)
Background: considering the dimension of the National Textbook Program (PNLD) in Brazil, the textbook plays a relevant role in student formation as iy, as in many countries, defines the real curriculum. Objective: to propose reflections on whether, and how, contextualized tasks can contribute to changing students' attitudes and beliefs regarding Mathematics and society. Design: In view of this goal, based on the assumptions of qualitative research. Settings and participants:. we analyzed a total of 41 Mathematics textbooks, 20 of which were Middle School and 21 of High School, all approved by the PNLD. Data collection and analysis: We sought for contextualized tasks that promoted reflections and critical discussions about everyday themes - economic, social, technological, sustainable, ethical, among others - present in society. To analyze the selected tasks, we adopted the Critical Mathematical Education as a theoretical lens, revealing social, political, and cultural concerns, proposing the reading of the world with Mathematics, in addition to promoting a Pedagogy for Liberation, based on social justice. Results: The results indicated that the selected tasks could promote reflections and contribute to the change of students' attitude towards Mathematics and society, however we emphasize that the teacher's role is fundamental in this process. Conclusion: In view of the high number of tasks present in Brazilian textbooks, we consider that they could present a greater number of contextualized situations, increasing the number of options for the teacher.
Keywords: Contextualized tasks; Critical Mathematics Education; Reading the world with Mathematics; Relevant teacher's role; Textbook analysis